A Phenomenological Study on Journaling in Developing Writing Skills among Young Professionals in Kidapawan City, Philippines - Rowena Sosas; Jennifer A. Arro; Howard V. Decasa; Danica Lou E. Magsico; Jan Marielle G. Maluyo; Rogie Mae P. Parillo; Marilyn P. Tungala (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2026)
Journaling is a component of writing macro skills in English, commonly practiced in educational settings. It lays the foundation for producing better and more polished writing. Despite this, there is a significant gap regarding the experiences of young Filipino professionals and their perceptions of the role of journaling in their writing development. To address this gap, the present study examines how journaling develops the writing skills of young professionals. Using a phenomenological research design, this study collected the data through in-depth interviews with nine participants residing in Kidapawan City, Philippines. They are aged 22 to 32, from diverse professional backgrounds, regardless of gender, and all have prior experience with journaling. Colaizzi-informed thematic analysis was used in data analysis. Results revealed that journaling developed the writing skills of young professionals in their writing competence, language use, self-expression, and logical reasoning. Additionally, journaling was found highly advantageous when consistently practiced, balanced between free-form writing and scaffolded prompts, and integrated with reflective thinking practices. Furthermore, young professionals engaged in journaling through format and medium selection, routine establishment, and individualized self-direction. Findings imply that journaling is an effective tool in developing writing skills among young professionals to support their personal and professional growth.